Structure and properties evolution of the Al – Cu – Mg alloy during the «twin-roll casting – hot deformation – heat treat-ment» technological process - Nohovitsyn, O. V.; Pryhunova, A. G.; Aiupova, T. A.; Nosko, O. A.; Volyniuk, D. A.; Ноговіцин, Олексій Володимирович; Пригунова, Адель Георгіївна; Аюпова, Тетяна Анатоліївна; Носко, Ольга Анатоліївна; Волинюк, Діана Артемівна (Харківський національний автомобільно-дорожній університет, 2024)
The influence of hot deformation and heat treatment on the wide solidification range 2024 alloy twin-rolled cast sheet billets structure and properties evolution at all stages of the technological process was studied. The maximum strength at a reduction ε = 50 % (ζB ≈ 450 MPa), and an increase in ductility with the degree of deformation (from 0–2 % in the cast state to 20–22 % after rolling and heat treatment) were established. The resulting mechanical properties of the 2024 alloy strip exceed existing analogs and standard requirements.
Еволюція структури та властивостей сплаву A-Cu-Mg під час технологічного процесу «розлив-прокатка – гаряча деформація – термічна обробка»
Keywords: Al-Cu-Mg alloy; Twin-roll casting; hot deformation; harderning; ageing.; сплав Al-Cu-Mg; розлив-прокатка; гаряча деформація; зміцнення; старіння; 621:746; 10.30977/BUL.2219-5548.2024.107.0.54